Carbon based catalysts - Etzold, Bastian J.M. (DGMK Tagungsbericht, 2016)
Catalytic materials are a key enabling technology. With their application chemical conversion can be accelerated, allowing for an economic operation, lower energy demand of the process and significantly reduced waste production due to their high selectivity. A majority of catalysts rely on porous materials, e.g. to spread an active component (often noble metals) within its pore system or to expose a high number of active site if the material itself is active. While porous carbon shows some important advantages (e.g. high specific surface area, tuneable surface chemistry, good chemical inertness, good electrical and thermal conductivity, easy recycling of active metals) the disadvantages of classical activated carbons prevented often to leverage these possibilities [1]. Major disadvantage of activated carbons is the low control of important properties like pore size distribution, pore volume, surface chemistry or impurity, due to the varying structure and quality of natural precursors (coconut shell, peat, etc.). Low oxidation stability e.g. needed for regeneration is an additional point for some applications. The development of nanostructured carbon allotropes, such as carbon nanotubes, demonstrated that these drawbacks can be overcome [2]. Even when focusing on non-nanocarbons from these findings design principles for the synthesis of new porous carbon materials for catalytic applications can be deduced. To achieve a high reliability of the material properties synthetic carbon precursors with reliable properties shall be employed. Furthermore, high specific surface area can be combined with good oxidation resistance for crystalline carbon materials. This contribution focuses on novel carbons for catalysis from powder to hierarchically structured shapes while employing carbides or polymers as reliable precursors [3, 4]. To be able to design suitable high performing catalytic materials, emphasis is given, in particular, to a knowledge-driven tuning of material properties during the synthesis like pore size, crystallinity and surface functionalization. As instructive example the application of porous carbons as solely catalysts for the dehydrogenation of ethylbenzene (EB) is discussed. In the past decade carbon nanomaterials were identified to be active and selective in the oxidative and non-oxidative dehydrogenation. Interestingly, for the later one coking could be suppressed even without the addition of steam [5]. In this contribution macroscopic carbon materials are presented achieving a similar selectivity and stability like nanocarbons while avoiding typical drawbacks of nanomaterials (unclear supply, unknown health risks, etc.) [6]. Through varying the synthesis temperature for titanium carbide-derived carbons (CDCs) between 800 and 1600 °C, carbons with properties ranging from a classical amorphous and microporous structure to a graphitic and highly mesoporous one were obtained. The CDCs were employed as catalysts for the non-oxidative dehydrogenation of EB at 550 °C and 20 h time-on-stream. The microporous and amorphous carbons show a selectivity below 85% and a constant deactivation during the experiment. A clear increase in selectivity and stability could be observed with increasing the pore size above 4 nm and the degree of graphitization. In combination with a post-synthesis nitric acid treatment catalysts were obtained reaching a selectivity of 95% without observable deactivation during the experiment. Furthermore, these high performing crystalline materials show excellent oxidation resistance (TG onset > 650 °C) allowing for a regeneration of coke deposits through burning if necessary.
CRIS-Team Scopus Importer:2023-08-15